Ion currents in embryo development. Issue 1 (16th March 2016) - Tosti, Elisabetta; Boni, Raffaele; Gallo, Alessandra
Abstract: Ion channels are proteins expressed in the plasma membrane of electrogenic cells. In the zygote and blastomeres of the developing embryo, electrical modifications result from ion currents that flow through these channels. This phenomenon implies that ion current activity exerts a specific developmental function, and plays a crucial role in signal transduction and the control of embryogenesis, from the early cleavage stages and during growth and development of the embryo. This review describes the involvement of ion currents in early embryo development, from marine invertebrates to human, focusing on the occurrence, modulation, and dynamic role of ion fluxes taking place on the zygote and blastomere plasma membrane, and at the intercellular communication between embryo cell stages. Birth Defects Research (Part C) 108:6–18, 2016. © 2016 Wiley Periodicals, Inc.